The Tri-Faith Initiative. Issue 1 (January 2019) - Alexander, Chris
Countryside Community Church is the primary Christian presence of the Tri-Faith Initiative in Omaha NE. This initiative is an intentional co-location of a synagogue, mosque, and church on the same 35-acre Commons area, for the purpose of being intentional neighbors and investing in interfaith friendships. Our vision is to Work together to build an environment of acceptance, respect, and trust; to challenge stereotypes of each other; to learn from one another; and to counter the influence of extremists and agents of hate. This article is a story of how we came to be neighbors and what we hope to accomplish.